Investigation the effect of pulsed laser parameters on the temperature distribution and joint interface properties in dissimilar laser joining of austenitic stainless steel 304 and Acrylonitrile Butadiene Styrene. (December 2019) - Peng, Yeping; Barzinjy, Azeez A.; Al-Rashed, Abdullah A.A.A.; Panjehpour, Afshin; Mehrjou, Mehdi; Afrand, Masoud
Highlights: Laser welding has changed the microstructure of the materials. The tensile shear load of the joint increased with laser power from from 280 to 460 N. By increasing the frequency, the number of bobbled at the ABS interface was increased. By decreasing the focal length, the surface temperature and the penetration rate were increased. With increasing the average power, the dimensions of the molten pool increased. Abstract: Direct laser joining of metal to plastic materials is one of the cost effective methods of joining. The demand for laser welding of stainless steels and thermoplastics is going on increase because of having many applications such as automotive, aerospace and aviation industries. This paper presents the experimental investigation of direct laser joining of stainless steel 304 and Acrylonitrile Butadiene Styrene (ABS). The effects of pulsed laser parameters including laser welding speed, focal length, frequency and power on the themperature field and tensile shear load was investigated. The results showed that excessive increase of the joint interface temperature mainly induced by high laser power density results in exiting of the more volume of the molten ABS from the stainless steel melt pool. Also, increasing the laser power density through decreasing the focal length or increasing the laser power led to an increase in the surface temperature, higher beam penetration and high volume of molten ABS. Decreasing the focal length from 5 to 2 mm significantly rose the temperature from 150 to 300 °C. By increasing the laser pulse frequency, the number of bobbles at the ABS interface surface remarkably increased where the temperature increased from 120 to 180 °C. The X-ray spectroscopy results showed the existence of the polymer elements on the metal surface at the joint interface zone. The tensile shear load clearly increased from 280 to 460 N with augmentation of laser average power from 180 W to 215 W. Applying higher levels of laser power has clearly decreased the tensile shear load due to creating bigger bobbles and more cavities at the adhesive zone.